Green business concepts, methodologies, tools, and applications (Business Science Reference, 2019)
"This book is a vital reference source for the latest research findings on the challenges and benefits of implementing sustainability into the core functions of contemporary enterprises, focusing on how green approaches improve operations in an ecological way. Highlighting a range of topics such as corporate sustainability, green enterprises, and circular economy"--